A new torsion control mechanism induced by blood circulation in dragonfly wings. (6th February 2015) - Hou, Dan; Yin, Yajun; Zhong, Zheng; Zhao, Hongxiao
Abstract: A new mechanism to generate the torque of flapping dragonfly wings is disclosed in this paper. The concept is inspired by blood circulation in insect wings. The blood flowing in veins induces Coriolis forces in the flapping wings. The Coriolis forces acting on veins are of opposite directions when blood flows in and out. The opposite Coriolis forces generate torsional moment to the wing, especially in the leading-edge part. To estimate the time-varying torque induced by the blood circulation, a simplified U-tube model is designed. A three-dimensional finite element model of the wing is developed to analyze the dynamic behaviors under this torque. The dragonfly wing is in favor of torsional deformation because the corrugated structure is of high flexural rigidity in the spanwise direction but is of low torsional rigidity in the chordwise direction. In both the downstroke and upstroke, the twist of the leading-edge part causes the sections to camber spontaneously. Such a kind of deformation is found to be of great importance to improve aerodynamic efficiency. In addition, it also compensates for the disadvantageous bending deformation caused by air pressure in flapping flight. These results are important for better understanding of the multifunctional structures of dragonfly wings and may give some inspiration to the bionics of flapping-wing micro air vehicles (FMAVs).